Right ventricular longitudinal strain on cardiovascular magnetic resonance imaging predicts outcome in patients undergoing transcatheter mitral valve repair. (14th October 2021) - Koschutnik, M; Dona, C; Nitsche, C; Dannenberg, V; Koschatko, S; Beitzke, D; Loewe, C; Huelsmann, M; Schneider, M; Bartko, P E; Goliasch, G; Hengstenberg, C; et al.
Abstract: Background: The prognostic value of left and right ventricular global longitudinal strain (LV and RV GLS) derived from cardiovascular magnetic resonance (CMR) feature tracking in patients with severe mitral regurgitation (MR) undergoing transcatheter mitral valve repair (TMVR) is unknown. Methods: Consecutive patients scheduled for TMVR underwent pre-procedural and follow-up CMR imaging including feature tracking strain analysis. Kaplan-Meier estimates and multivariate Cox-regression analyses were used to identify the prognostic impact of LV and RV GLS on CMR using a composite of heart failure hospitalization and death. Results: A total of 62 patients (78.3±7.0y/o, 45% female, EuroSCORE II: 9.7±7.2%) with severe MR underwent CMR prior to TMVR. 23 (37%) patients presented with right ventricular dysfunction (RVD) defined by RV GLS >−20% on CMR. At baseline, RVD was associated with NT-proBNP levels (9510 vs. 4064pg/mL, p=0.030). On CMR, RVD was associated with reduced left and RV ejection fraction (LVEF: 39.2 vs. 48.7%, p=0.011, RVEF: 35.1 vs. 46.7%, p<0.001), as well as increased LV GLS (−14.0 vs. −19.5%, p=0.003). A total of 18 events (12 deaths, 6 hospitalizations for heart failure) occurred during follow-up (mean 11.4±9.1months). While LV GLS was not significantly associated with outcome (HR 0.95, 95% CI: 0.90–1.01, p=0.082), RV GLS showed a strong and independent association with event-free survival by multivariate Cox-regression analysis (adj.HR 0.91, 95% CI: 0.83–0.99, p=0.033) after adjustment for relevant baseline and procedural data (EuroSCORE II, post-procedural residual MR), imaging parameters (TAPSE, LV and RVEF on CMR), and cardiac biomarkers (NT-proBNP). When compared with the "gold standard" RVEF on CMR (RVEF <45%: adj.HR 0.86, 95% CI: 0.23–3.20, p=0.825) and TAPSE on echo (TAPSE <17mm: adj.HR: 2.77, 95% CI: 0.72–10.70, p=0.140), only RVD (RV GLS >−20%: adj.HR 5.05, 95% CI: 1.23–20.63, p=0.024) was significantly associated with the composite endpoint (Figure 1). Follow-up CMR was performed in 21 (34%) patients. RV GLS significantly improved after TMVR (−20.6 to −25.2%, p=0.016, Figure 2). Conclusions: RV rather than LV GLS, as determined on CMR, is an important predictor of outcome in patients undergoing TMVR. At 1 year follow-up, RV function significantly improved, and thus might add useful prognostic information on top of established risk factors. Funding Acknowledgement: Type of funding sources: None.